Model of the Influence of Training and Discipline on Karate Athletes' Achievement with Motivation as an Intervening Variable - Agustus Agustus; Edizal Edizal; Sari Sakarina (Indonesian Economic Review, 2026)
This study aims to analyze the effect of training and discipline on motivation and its implications for the athletic performance of karate athletes at the Banyuasin Regency Youth, Sports, and Tourism Office. The study uses a quantitative approach with a causality design. The study population consisted of 52 karate athletes, and the entire population was sampled using a census method. Data collection was conducted through a questionnaire with a five-point Likert scale that measures the variables of training, discipline, motivation, and athlete performance. Data analysis used the Partial Least Square (PLS) method with the help of the SmartPLS application through outer model and inner model testing. The results showed that training and discipline had a positive and significant effect on athlete motivation. In addition, training and discipline also have a positive and significant effect on the athletes' performance. Motivation was found to have a positive and significant effect on the athletes' performance and was able to mediate the effect of training and discipline on the karate athletes' performance. The findings of this study emphasize the importance of improving the quality of training programs, implementing consistent discipline, and strengthening the athletes' motivation to optimize their athletic performance.